Hydrazine as efficient fuel for low-temperature SOFC through ex-situ catalytic decomposition with high selectivity toward hydrogen - Song, J.; Ran, R.; Shao, Zongping (Elsevier Ltd, 2010)
Hydrazine is a promising fuel for portable fuel cells because it is a liquid, it is carbon free and it has a high energy density. In this work, hydrazine was investigated as an efficient fuel for low temperature solid-oxide fuel cells (SOFCs) with a traditional nickel anode. A catalytic system with high selectivity toward hydrogen was developed using Ba0.5Sr 0.5Co0.8Fe0.2O3-d (BSCF) as the main catalyst and potassium hydroxide as the promoter. The result of compositional analysis of the products showed that the hydrazine can be decomposed into hydrogen and nitrogen with 100% selectivity when an appropriate amount of KOH promoter is used. Acceptable power densities were achieved for a thin-film samaria-doped ceria (SDC) electrolyte cell operating on hydrazine decomposition products and hydrogen over a complete operation temperature range of 650-450 °C. In addition, a similar cell with ammonia as the fuel displayed a much lower performance. © 2010 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.